Peculiarities of vanillin release from amino-functionalized mesoporous silica embedded into biodegradable composites. (April 2017) - Stanzione, M.; Gargiulo, N.; Caputo, D.; Liguori, B.; Cerruti, P.; Amendola, E.; Lavorgna, M.; Buonocore, G.G.
Graphical abstract: Highlights: Amino-functionalized mesoporous silica is able to form imine bond with active compound vanillin. Active mesoporous silica is well dispersed into the polymeric biodegradable matrix. Vanillin release can be easily controlled and triggered by the simple addition of water in ethanol. Abstract: Mesoporous silica nanoparticles are among the most promising nanovectors for controlled release of active compounds. In this work we design a mesoporous silica-based delivery system in which the release of the active compound is controlled by specific pore/wall interactions and can also be triggered by an external stimulus, such as the simple addition of water into the surrounding releasing medium. Due to its reversibility in presence of water, imine bond formation between amino groups and aldehydes has been proposed as a valuable approach to reach this scope. The amino-group is provided by the amino-functionalized mesoporous silica which has been obtained through the functionalization of Santa Barbara Amorphous (SBA)-15 with aminopropyltrietoxysilane. Whereas the aldehyde is represented by the active compound itself: the natural antimicrobial vanillin. The obtained particles have been embedded into PCL-based films. The amino-functionalization of mesoporous silica has been confirmed through NMR analysis and X-ray diffraction. Imine bond formation and evolution has been followed by 13 C NMR before and after the contact of mesoporous silicas with water. Release kinetics of vanillin show that the diffusion of vanillin from films containing the functionalized mesoporous silica is delayed by about 20% and 75% with respect to films containing free vanillin, in water and in ethanol respectively. The most significant feature of the system is the stepwise behavior which shows that the release of the amount of vanillin bound to the NH2 groups of functionalized SBA is triggered only after the addition of water to the surrounding ethanolic solution. These findings give an important insight into the use of pristine and functionalized mesoporous silicas for the development of polymer films for active responsive packaging materials.